2020
DOI: 10.1038/s41598-020-78945-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, functional characteristics, and clinical significance of right ventricular involvement in patients with hypertrophic cardiomyopathy

Abstract: We sought to investigate the prevalence, functional characteristics, and clinical significance of right ventricular (RV) involvement in patients with hypertrophic cardiomyopathy (HCM). A total of 256 patients with HCM who underwent both cardiac magnetic resonance (CMR) imaging and transthoracic echocardiography within 6 months of each other were retrospectively analysed. RV involvement was defined as an increased RV wall thickness ≥ 7 mm on CMR in the segments of the RV free wall. Primary outcomes were defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 27 publications
3
23
1
Order By: Relevance
“…Moreover, Badaran et al used vector velocity imaging and showed severe displacement incorrectness at all levels of RV in HCM adults [ 22 ]. Our study is the first to demonstrate an impairment of RV mechanics in the childhood HCM population by means of CMR-FT. Our results of CMR-FT-derived RVGLS are slightly higher than the values obtained with echocardiography in adults [ 29 ]. Interestingly, in the study by Cincin et al, unlike in our study, LVOT obstruction in HCM was not associated with the impairment of RV mechanics [ 28 ].…”
Section: Discussioncontrasting
confidence: 82%
“…Moreover, Badaran et al used vector velocity imaging and showed severe displacement incorrectness at all levels of RV in HCM adults [ 22 ]. Our study is the first to demonstrate an impairment of RV mechanics in the childhood HCM population by means of CMR-FT. Our results of CMR-FT-derived RVGLS are slightly higher than the values obtained with echocardiography in adults [ 29 ]. Interestingly, in the study by Cincin et al, unlike in our study, LVOT obstruction in HCM was not associated with the impairment of RV mechanics [ 28 ].…”
Section: Discussioncontrasting
confidence: 82%
“…Assessment of RV systolic function: Patients with RV involvement had more impaired LV global LS, RV global LS, RV septal wall LS, and RV free wall LS than those without RV involvement. RV global LS ( R = .345, P < 0.001) and RV free wall LS ( R = .310, P < 0.001) were significantly correlated with RV maximal WT 45 …”
Section: Establishment Of the Diagnosis Of Hcmmentioning
confidence: 93%
“…Pressure across RVOT is measured in parasternal short axis or parasternal RV outflow view. Mid‐base obstruction in the RV is characterized by a prominent hypertrophied septal band. Doppler signal appears relatively symmetric and dome‐like and not dagger‐shaped like LVOT obstruction. Assessment of RV systolic function: Patients with RV involvement had more impaired LV global LS, RV global LS, RV septal wall LS, and RV free wall LS than those without RV involvement. RV global LS ( R = .345, P < 0.001) and RV free wall LS ( R = .310, P < 0.001) were significantly correlated with RV maximal WT 45 The RV E/A ratio is lower and the RV isovolumetric relaxation time and RV deceleration time are significantly prolonged in patients with HCM 43 …”
Section: Establishment Of the Diagnosis Of Hcmmentioning
confidence: 94%
See 1 more Smart Citation
“…RV strain assessment was shown to be feasible and biventricular involvement indicated by an impaired RV strain was associated with adverse outcome in HCM patients [70,71]. With HCM not only affecting ventricular morphology but also inducing atrial enlargement, especially LA function and abnormalities have been shown to characterise different stages of the disease.…”
Section: Cmr-ft In Non-ischemic Cardiomyopathiesmentioning
confidence: 99%